2009
DOI: 10.1007/s00464-009-0569-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery significantly reduces surgical-site infections compared with open surgery

Abstract: In US academic medical centers, laparoscopy significantly reduces SSI. Patients treated with laparoscopic procedures are less likely to experience SSI. After stratification by severity of illness, admission status, and wound classification, laparoscopic techniques showed a protective effect against SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
4
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 21 publications
6
94
4
7
Order By: Relevance
“…The management of many diseases is the benefit of the application of laparoscopic approach. Laparoscopic appendectomy is an increasing procedure in popularity since initially reported by Semm in 1983 (9). Several studies have shown the advantages of laparoscopic surgery in terms of shorter hospital stay, rapid postoperative recovery, and better pain control (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The management of many diseases is the benefit of the application of laparoscopic approach. Laparoscopic appendectomy is an increasing procedure in popularity since initially reported by Semm in 1983 (9). Several studies have shown the advantages of laparoscopic surgery in terms of shorter hospital stay, rapid postoperative recovery, and better pain control (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In open surgery of the abdomen, the trauma of laparotomy wounds is a source of infection or dehiscence and may increase the likelihood of post-operative chest infection, ileus and immobility [30]. The evolution of new minimally invasive approaches, such as Minimally Invasive Surgery (MIS) and Single Incision Laparoscopic Surgery (SILS), allows to perform the surgery by bringing the surgical instruments and endoscope to the surgical site through few or only one small incision, improving the physiological and immuno responses with respect to open surgery [6], and reducing the trauma, without compromising the surgical quality [27,31].…”
Section: Introductionmentioning
confidence: 99%
“…The longterm impact on oncological endpoints awaits the findings from large ongoing randomised trials. Table 2 Two recent studies [125,126] have shown the definitive advantage of laparoscopic approach in terms of incidence and severity of postoperative surgical-site infection (SSI). Varela et al [125] Postoperative morbidity after laparoscopic approach to the rectum seems to be similar/slightly lower than after open surgery.…”
Section: 7% [Consensus]; Gor A: 857% [Consensus])mentioning
confidence: 99%